SIKAP MAHASISWA FISIP UNSRAT TERHADAP JASA LAYANAN UPT PERPUSTAKAAN UNSRAT - Golung, Anthonius M. (ACTA DIURNA KOMUNIKASI, 2015)
The aim of this research is to evaluate the attitude of FISIP students in making use the Sam Ratulangi University UPT library service. It involves so respondent who have used this library service. It’s result shows that FISIP students attitude towards the library service is positive. It can be seen in percentage. The circulation of the service shows 24% Very good, 72% Good, 4% Bad. The reference of the service shows 10% Very good, 88% Good and only, 2% Bad. The magazine and newspaper service shows 12% Very good, 80% Good and 8% Bad. Internet service shows 16% Very good, 60% Good and 24% Bad. Observation service shows 88% Very good, 12% Bad. On the other side students also has their negative at hide avowers the providing of the books and not being relevant with their needs. Keywords : Evaluate the attitude, Library service